(untitled) (Al-Qamar, 2022)
Physical attractiveness is known to be associated with several socially desirable outcomes. With the growing emphasis on beauty in media and other platforms, attractiveness related concerns are becoming more common in today’s world, making the problem an intensified clinical condition. In the current study, data was collected and analyzed quantitatively to analyze the difference in levels of Charismaphobia between Muslim women who cover their heads and faces when going outside and those who do not cover their heads and faces in any form when they go out. Using convenient sampling method, data was collected from 615 Muslim women who filled out paper questionnaires as well as online survey. Unveiled Muslim women were found to exhibit higher level of Charismaphobia than veiled Muslim women. Differences based on marital status, professional level, body shape and skin tone were also analyzed in terms of Charismaphobia. The study has its valuable implications in understanding the condition of Charismaphobia more, especially as it exists in Pakistan and to explore ways to manage and treat it.